Research Trends on Digital Marketing Strategies and Student Satisfaction in Higher Education: A Bibliometric Analysis - Sir , Víctor Manuel Valdiviezo; Salazar, Carlos Alberto Hinojosa; Paco, Edwin Gonzales; Huamán, Sara Emilia Remuzgo; Peña, Lida Inés Carhuas; Chichipe , Marlyn Danila Perez (Journal of Ecohumanism, 2024)
The main objective of this bibliometric article is to analyze and synthesize existing research that explores the relationship between digital marketing strategies implemented by higher education institutions and the satisfaction perceived by students. A bibliometric methodology was adopted, constructing a canonical search equation in the Scopus database, without temporal restrictions. The extracted data were processed using Bibliometrix and VOSviewer to create scientific maps and perform statistical analyses. The main results reveal a significant growth in scientific production, with a total of 1126 published papers and a remarkable international collaboration. The central concepts are social networks, e-commerce, student satisfaction and digital marketing. An interdisciplinary nature is observed, with contributions from various areas of knowledge. Although the interest is global, the growing participation of Middle Eastern nations stands out. In conclusion, the field of digital marketing research on college students has experienced significant growth, reflecting the adoption of digital technologies in higher education and the need for effective digital marketing strategies to attract and retain students.